The Strategic Used of Cyberspace by Narco-Terrorist Groups Belonging to Kuki-Chin-Mizo’s in The Western Southeast Asia. - Alka Singh; Ghanashyam (Thoujal) Khumancha Oinam; Yengkhom Ronald Ronald (Jurnal ISIP: Jurnal Ilmu Sosial dan Ilmu Politik, 2026)
This article explores the practical use of cyberspace by Narco-terrorist groups in Western Southeast Asia, to trouncing the physical limitation and legal barriers put up by Governments. The article employed Duncan Snidal's rational choice in international relations theory, Examining the rationale behind the use of cyberspace by narco-terror. Using the qualitative literature review method, the article integrates academic works and credible sources to analyse the phenomenon. The article found that narco-terrorist belong to Kuki-Chin-Mizo's community had used cyberspace for various illegal activities, right starting from selling drugs, procurement weapons, contacting with its sponsors, and development of propaganda. The article concludes it is virtually impossible for any state to legally regulate cyberspace to entirely prevent illicit activities.